Self-taught and the educational system: a more than necessary dialogue (Research, Society and Development, 2022)
This is an article with the objective of analyzing the importance of the dialogue between the Brazilian educational system and self-learning, based on the acquisition of new knowledge, given the advance of information technology and globalization. A reflection presented in a descriptive way in three topics: The contemporary world: globalization and technology; Teaching-learning: the road traveled; Learning in the time of technologies. Globalization and technology are intrinsically linked to the access to knowledge, the teacher as the mediator of the teaching-learning process assumes the role of mediator and the students are the protagonists. Self-learning is the pedagogical tool at the disposal of teachers so that public policies advance and enable equal access to knowledge through the network. We conclude that it is up to each teacher to find their own way to innovate, to keep up with trends, and to offer their students all the possibilities to develop their skills and competencies.